Analisa Pengendalian Persediaan Sepatu Pada PT. Buccheri Indonesia Menggunakan Metode Economic Order Quantity - Sretiani, N K; Jaya, A I; Nacong, N (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2020)
PT. Buccheri Indonesia is a company engaged in the sale of shoes, sandals and bags. These days the high level of competition in the shoes and sandals industry makes every manufacturer of shoes and sandals must pay close attention to market changes. Inventory is the most important thing in a company and has an important influence on business functions, especially the operational functions of marketing, which includes ordering costs and storage costs, so inventory optimization is needed. In this study, the author uses the Economic Order Quantity method to optimize shoes inventory. This study aims find to are out the point of reorder, order frequency, and comparison between company policy and Economic Order Quantity method. PT. Buccheri Indonesia stipulates the number of orders on each time order is 5,943 pairs of shoes, with the frequency of ordering 48 times/year, and the inventory’s total cost is Rp.406,843,938. While using the Economic Order Quantity method the number of orders on each time is 7,214 pairs of shoes, the frequency ordering 39 times/year, and the inventory’s total cost is Rp.396,776,965.06. So, the difference cost of company policies and by using the Economic Order Quantity method, is Rp.10,066,972.94,-